2019
DOI: 10.1007/s00330-019-06399-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety, and long-term efficacy of stereotactic radiofrequency ablation for tumors adjacent to the diaphragm in the hepatic dome: a case-control study

Abstract: Objectives Achievement of adequate treatment margins may be challenging when the target is either difficult to visualize, awkward to access, or situated adjacent to vulnerable structures. Treatment of tumors located close to the diaphragm in the hepatic dome is challenging for percutaneous radiofrequency (RF) ablation for these reasons. The purpose was to assess the feasibility, safety, and clinical outcome of multi-probe stereotactic RF ablation (SRFA) of liver tumors in the subdiaphragmatic area. Methods Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…First clinical reports on stereotactic percutaneous ablation of liver tumors are available (22)(23)(24)(25), as well as several comparative studies highlighting the accuracy and efficiency of using navigation technology vs. conventional image guidance for tumor targeting (26,27). While little is known about factors influencing targeting accuracy and therapeutic efficacy when using such navigation systems for stereotactic tumor targeting, they likely facilitate accessibility and treatment of traditionally difficult to target liver tumors (28). Our group has previously reported the benefits of using stereotactic imageguided microwave ablation (SMWA) in the treatment of HCC (29).…”
Section: Introductionmentioning
confidence: 99%
“…First clinical reports on stereotactic percutaneous ablation of liver tumors are available (22)(23)(24)(25), as well as several comparative studies highlighting the accuracy and efficiency of using navigation technology vs. conventional image guidance for tumor targeting (26,27). While little is known about factors influencing targeting accuracy and therapeutic efficacy when using such navigation systems for stereotactic tumor targeting, they likely facilitate accessibility and treatment of traditionally difficult to target liver tumors (28). Our group has previously reported the benefits of using stereotactic imageguided microwave ablation (SMWA) in the treatment of HCC (29).…”
Section: Introductionmentioning
confidence: 99%
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
“…Four propensity score matched analyses compared stereotactic thermal ablation for different subtypes of patients or lesions. Stereotactic RFA yielded similar safety and treatment e cacy outcomes when comparing CT 'invisible' tumours ablated with MR image fusion to CT visible tumours (30), octogenarians to a younger study population (36), lesions in a subphrenic location to non-dome locations (39) and HCC in a subcardiac position to a non-subcardiac location (40).…”
Section: Comparative Studiesmentioning
confidence: 91%
“…To achieve the most accurate probe position, navigation systems can be a helpful tool 7 13 . An accurate placement of the probe is a precondition for a high primary efficacy.…”
Section: Discussionmentioning
confidence: 99%